Preliminary Diagnosis About the Appeal's Suppression in the Brazilian New Code of Civil Procedure - Merigueti, Diego Souza (2016)
The phenomenon of sluggishness in the judicial system reveals an attack to justice. In this purpose, this article aims to analyze the appeal's suppression in the brazilian new Code of Civil Procedure, as a way able to reach the scope of giving celerity to the jurisdictional protection in Brazil. At the diagnosis proposed, it will be presented possible legal consequences arising from the limitation of the "Agravo de Instrumento" and from the abolition of both "Agravo Retido" and "Embargos Infringentes" in the procedural diploma newly sanctioned. Unfolding this analysis, it is worth highlighting the contemporary movement to perform constitutional values and guarantees in procedural legislation, including the reasonable duration of the proceeding. This paper was produced by analyzing concepts and in consultation to national and foreing books, from authors of recognized contribution to the field, as well as through the study of the new procedural law, why it is therefore a literature review and a qualitative analysis.